PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR SISWA KELAS IV DI SEKOLAH DASAR - Wulan Maulidia; Rarasaning Satyaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the learning process that involves various activities and actions that need to be done by students to obtain good learning outcomes. In this situation, to overcome learning obstacles and help students relate the material to everyday life, it is important to choose the right model. Therefore, the Contextual Teaching and Learning learning model is expected to be able to apply the knowledge and skills learned and relate the material to real-life experiences. The selection of the Contextual Teaching and Learning model has a positive impact by encouraging active student participation, increasing understanding and facilitating the application of knowledge in real situations. This study uses a quantitative approach with a quasi-experimental design form that uses a posttest only control design research design. The population in this study were all fourth- grade students of SDN Margerejo 1 Surabaya. The sample was taken using Probability Sampling so that class IV-A was selected as the experimental class and class IV-C as the control class. The data collection technique used was a student learning outcome test. The data analysis technique used the Mann- Whitney. Based on the results shown by the statistical analysis of SPSS Version 25, it was found that there was no influence of the Contextual Teaching and Learning Model on the Learning Outcomes of Pancasila Education for Grade IV Students in Elementary Schools.